Effect of Foliar by Applied Moringa Leaf Extract on Tomato Growth Performance under Drought Stress - Batool, Rida; Farzand, Muqaddas; Ali, Hazib; Ashraf, Adeela; Awais, Muhammad; Khalid, Fiza (Indus Journal of Bioscience Research, 2025)
Among stresses, drought is a fatal that causes threats to crops. Drought stress is a significant constraining element in tomato manufacturing, affecting plant development, yield, and fruit excellence. Therefore, scientists have been utilizing numerous tactics to mitigate the damaging consequences of water deficit. Plant growth promoters such as extract from moringa leaves are often utilized exogenously to vegetation to promote their resistance to numerous abiotic stresses. Three varying dosages of extract from moringa leaves 0%, 3% as well 6% were sprayed to the tomato (Solanum lycopercium) crop. The experiment was CRD designed with three replications. Drought (45% FC) was applied to determine the toxic impact on growth variables and the physiology of tomato. The data noted during the study was assessed for variance by utilizing CO_ STAT software. Results demonstrated that drought diminished all growth metrics and ion contents. During drought conditions, moringa-treated plants had improved growth factors and physiochemical attributes such as soluble sugar, flavonoids, anthocyanin, ascorbic acid, chlorophyll, and ion contents. MLE application increased proportionate amounts of proline and water, suggesting improved water retention and stress tolerance. Increased antioxidant enzyme activity in treated plants also indicated a bolstered defense mechanism against drought-induced oxidative stress. Foliar application of Moringa leaf extract demonstrates promising potential as a sustainable agronomic method to enhance tomato expansion and stress resilience under drought conditions. The 6% moringa leaf extract had a greater impact on all measured variables. It was stated that Leaf extract from moringa can be utilized as a development promoter because this can optimize the morpho-physiological attributes as well as biochemical features of tomato by lessening the destructive effects of drought. It was stated that extract from moringa leaves can be utilized as a growth-promoting agent because it can optimize the morpho-physiological attributes as well as biochemical features of tomato by lessening the destructive effects of drought.